Financing global development: Beware of `end poverty' euphoria and trigger-happy reform of concessional finance - Christopher Garroway; Helmut Reisen (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The UN Conference on Financing for Development in Addis Ababa in July 2015 will pave the way for the implementation of the post-2015 development agenda. The Briefing Paper series “Financing Global Development” analyses key financial and non-financial means of implementation for the new Sustainable Development Goals (SDGs) and discusses building blocks of a new framework for development finance. The client base of the concessional finance windows at the major multilateral development banks is shrinking as some of the largest borrowers by volume become richer, more credit-worthy and lose eligibility for `soft' financing terms. Simultaneously, competition from new donors is growing, as is demand from low-income and lower middle-income countries for market-priced sovereign borrowing, spurred on by prevailing low-interest rates. Pressure to adapt to this changing operational context notwithstanding, the uncertainty facing the development finance industry suggests a gradualist, precautionary and insurance-oriented approach to the future of multilateral concessional windows. A realistic assessment of medium-term growth prospects suggests that the pool of countries eligible for multilateral `soft' finance windows will shrink slowly over the coming decade. In such a scenario, the number of people living in extreme poverty by 2025 would still amount to more than half a billion, with a sizable share living in middle-income countries that will be ineligible for concessional finance by current eligibility rules. This Briefing Paper argues that trigger-happy reform suggestions for shrinking or scaling back multilateral finance are unrealistic and counterproductive: they ignore the option value of preserving international financial institutions and their concessional windows in a world with considerable uncertainty about future poverty outcomes and global governance failures that prevent first-best policy solutions. Strategic options exist for the shareholders of the World Bank, the African Development Bank, the Asian Development Bank and the International Monetary Fund to attenuate the dilemma they face from their shrinking client base. These options are: redefining concessional fund eligibility criteria, so that it reflect more closely national capacity to raise domestic resources; smoothing transition periods by making `blend status' an explicit step in the graduation process, with funds directed towards measures of social inclusion and redistribution; strengthening sub-sovereign allocation, to take account of within-country regional inequalities; opening the multilateral soft windows for regional and global public goods, with climate change adaptation and disaster risk management as tracer sectors.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Agenda 2030